Operation of the fiscal council in the governance process in a credit cooperative (Research, Society and Development, 2020)
This article aims to verify governance, in a credit cooperative, inserted in a reality with major changes in society, which generate a diversity of views, attitudes, conflicts, in the experience of management. These challenges become part of the object of study, in order to understand how it is possible to adopt practices that can assist the Fiscal Council in the governance process. To answer this concern, the study relies on methodological paths: the qualitative approach, which verifies the working relationships, of the Supervisory Board, as a supervisory body, in the search for transparency, austerity in the use of resources, in the elaboration of strategies for the Board of Directors. Still, the research contemplates a theoretical set, based on the sciences. The survey results were enriched with semi-structured interviews with the Fiscal Council. The findings included a crossing of information, with theoretical references. The conclusions indicate that the governance environment, develops in a permanent, fertile dialogue for accountability, transparency, as well as cultivating a strategic work of responsibility, of planning the cooperative, which allows pointing out that the governance process is gaining a acceptable level of professional maturity in the credit union.